Tomato arabinosyltransferase prevents precocious senescence - Ho-Young Jeong; Yoonseo Lim; Myeong-Gyun Seo; Soon Ju Park; Chanhui Lee; Young-Joon Park; Choon-Tak Kwon (Horticultural Plant Journal)
Senescence, a crucial developmental process in the life cycle of plants, involves programmed destruction of cellular components of leaves. The onset of senescence is synchronized with other developmental processes for successful reproduction since senescence eventually leads to cell death. Arabinosyltransferase FASCIATED AND BRANCHED 2 (FAB2) is known to control meristem proliferation. Here, we show that FAB2 could inhibit premature leaf senescence in tomato plants. Both chemically mutagenized and CRISPR-generated fab2 mutants exhibited excessively accelerated senescence, which resulted in sterility. Transcriptome analysis revealed that FAB2 extended leaf longevity by suppressing transcription of genes highly expressed in mature leaves. Transcription of FAB2 was increased in younger leaves, potentially inhibiting premature leaf senescence. The precocious senescence of fab2 mutants was in contrast to fasciated inflorescence (fin) mutants, which carried mutations in a hydroxyproline O-arabinosyltransferase gene, leading to meristem overproliferation. Our observations indicate that complex genetic hierarchy in the cascade of tomato arabinosyltransferases could control different aspects of developmental processes such as stem cell proliferation and senescence.